Current status, challenges and the way forward for clinical pharmacy service in Ethiopian public hospitals - Arebu Issa Bilal; Zelalem Tilahun; Gebremedhin Beedemariam Gebretekle; Belete Ayalneh; Bisrat Hailemeskel; Ephrem Engidawork (BMC, 2017)
Abstract Background Clinical pharmacy service has evolved steadily over the past few decades and is now contributing to the 'patient care journey' at all stages. It is improving the safety and effectiveness of medicines and has made a significant contribution to the avoidance of medication errors. In Ethiopia, clinical pharmacy service is in its initial phase, being started in July 2013. This study therefore aimed at assessing the status, challenges and way forward of clinical pharmacy service in the country. Methods A cross-sectional survey was conducted in six regional states and one city- administration in September 2014. A total of 51 hospitals were included in the study. Both qualitative and quantitative methods were employed for data collection. Results A total of 160 pharmacy graduates, and 51 pharmacy heads participated in the study. Internal Medicine and Pediatric wards were the major wards where the graduates provide clinical pharmacy service. Almost 94% of the new graduates were found to be involved in clinical pharmacy service, but 47% of them rated their service as poor. The overall satisfaction of the graduates was close to 36%. Thirteen hospitals discontinued and two hospitals not even initiated the service largely due to shortage of pharmacists and lack of management support. About 44% of the surveyed hospitals documented the clinical pharmacy service provided using either developed or adopted formats. Lack of awareness by the medical fraternity, high attrition rate, lack of support from the management as well as from the health care team, readiness of the graduates to deliver the service, and shortage of pharmacists were identified by the key informants as the major stumbling block to deliver clinical pharmacy service. Conclusion Clinical pharmacy service is initiated in most of the surveyed hospitals and a large proportion of the graduates were involved in the service. Although there is a great enthusiasm to promote clinical pharmacy service in the surveyed hospitals, efforts made to institutionalize the service is minimal. Thus, concerted efforts need to be exerted to promote the service through organizing awareness forums as well as revisiting the curriculum.